PENAFSIRAN AGUSTINUS TERHADAP ROMA 5:12 DAN TRANSFORMASI HAMARTOLOGIS - Nainggolan, Jeppri; Gesika (STT-RAI Batam, 2024)
Man is God's noblest creation with specific graces, namely free will and reason. However, this free will has led man to sin, believing that all of man has fallen into sin. Originally, man was created in the image of God with a consciousness of transcendence. In Christianity, sin has a contagious force that is difficult to contain. This research uses qualitative methods with a descriptive approach to answer research problems with literature sources such as books, journals, and articles. The aim is to provide an overview of how digitization affects the beliefs and practices of Christianity. The transformation of hamartology in early Christianity shows a change in views about sin during the development of Christianity. Early understanding was influenced by Jewish tradition with the Torah as a way of obtaining forgiveness of sins. Augustine saw original sin as coming from Adam and Eve, inherited by every human being. The nature of sin is thought to be rooted in man's free will conditioned to sin. Augustine recognized the importance of free will but stated that human will is conditioned by original sin. Redemption is possible only through God's grace and faith in Christ.